International Press Correspondence. Vol. 18, no. 24, Special Spain number. - Dimitrov, Georgi, 1882-1949 ; Ibárruri, Dolores, 1895-1989 ; Pollitt, Harry (London : H.R.G. Jefferson)
1938-05-17 SA15-008-030 [519-602] pages : illustrations ; 28 cm. 15X/1/132/25